Kualitas Fermentasi Silase Ransum Komplit Berbasis Hasil Samping Jagung, Sawit dan Ubi Kayu - Lendrawati Lendrawati; Nahrowi Nahrowi; M Ridla (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
The study was conducted to evaluate fermentation quality of complete feed silage based on corn, palm and cassava by products. Each complete feed was ensiled separately in 50 litres silo and were opened 6 weeks after ensiling. The silage products were evaluated in terms of physical (colour, smell, and presence of moulds), chemical (pH, N-amonia content, WSC loss and dry matter loss) and microbial properties (number of lactic acid bacteria). The data was analyzed by using Completely Randomized Design with three treatments and six replications, followed by LSD test. The result showed that all complete feed silage treatments were having good quality. Fermentation quality of silage was affected with  kind of complete feed silage (P<0.05). In general, all of treatments had good fermentation quality of silage, because it have lower pH, ammonia content, WSC loss and dry matter also. It is concluded that quality fermentation of complete feed silage based on corn, palm and cassava by products had good quality and can be recomended as ruminant feeding.